Control-Flow Analysis of Functional Programs - Midtgaard, Jan (BRICS Report Series, 2007)
We present a survey of control-flow analysis of functional programs, which has been the subject of extensive investigation throughout the past 25 years. Analyses of the control flow of functional programs have been formulated in multiple settings and have led to many different approximations, starting with the seminal works of Jones, Shivers, and Sestoft. In this paper we survey control-flow analysis of functional programs by structuring the multitude of formulations and approximations and comparing them.